Pengaruh Komite Audit, Dewan Komisaris, Audit Tenure Dan Leverage Terhadap Integritas Laporan Keuangan - Citra Adlina Fiorenza; Syamsuri Syamsuri (CV. ITTC INDONESIA, 2025)
This study was conducted to determine the effect of the Audit Committee, Board of Commissioners, Audit Tenure, and Leverage on the Integrity of Financial Statements. This study was conducted on banking sub-sector companies listed on the Indonesia Stock Exchange in 2019-2023. In this study uses panel data regression. Sample selection was carried out using the purposive sampling method from secondary data in the form of financial statements and found 33 sample companies with 5 years of observation, so that the total sample in this study was 165 financial statements. Hypothesis testing was carried out using the Eviews 12 application. The results of this study Simultaneously the Audit Committee, Board of Commissioners, Audit Tenure and Leverage have an effect on the Integrity of Financial Statements. indicate that partially the Audit Committee has no effect on the Integrity of Financial Statements. The Board of Commissioners has no effect on the Integrity of Financial Statements. Audit Tenure has no effect on the Integrity of Financial Statements. Leverage have an effect on the Integrity of Financial Statements.